Pengaruh Efficiency, Privacy, Reliability, Emotional Benefit, dan Customer Service terhadap E-Satisfaction Pengguna Aplikasi Kereta Api Indonesia (KAI) Access - Farhan Azmi; Citra Kusuma Dewi (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2020)
KAI Access is an official mobile application of PT.KAI that aims to facilitate customers for purchasing tickets or accessing information about the train online. However, this application still facing several issues and have some impact on customer satisfaction. The purpose of this study is to determine the effect of efficiency, privacy, reliability, emotional benefit, and customer service on e-satisfaction of KAI Access users. This research is using a quantitative method by using descriptive and causal approach. This study using non-probability sampling with purposive sampling technique and samples taken were 107 respondents who are KAI Access application’s active users. This study using multiple linear regression analysis. The results show that efficiency, privacy, reliability, emotional benefit, and customer service simultaneously have a positive and significant impact on e-satisfaction. Partially, only the variables efficiency, emotional benefit, and customer service have a positive and significant impact on the e-satisfaction variable.